Abnormal plumage in possibly senile female Eiders Somateria mollissima - Swennen, C; Duiven, P; Wintermans, G J M (Wildfowl, 1989)
A collection of 460 Eiders that had fallen victim to an oil-pollution incident in the Wadden Sea in January 1987 was studied. Three individuals, initially classified as 2nd-calendar-year males on the basis of plumage characteristics, had divergent patterns on head and wing. Autopsies revealed that all were adult females: they had no testis and no bursa Fabricus, but an ovarium with a convoluted oviduct and female bulla ossea. It was concluded that the birds had a disturbed hormone balance, and probably were senile. Following these observations, two such birds were found among 43 dead Eiders that had been washed ashore on Texel in the winter of 1987-88 and another was discovered alive among a group of adult, non-breeding Eiders in the Vlieland colony (The Netherlands) in May 1987. None of these c. 7500 breeding females handled for ringing during the past 25 years showed any sign of a male-like plumage. It may well be that such birds are more common in the non-breeding group, but that they have been misidentified as immature males during former field observations. The findings suggest that some females from the non-hunted Dutch Eider population may die of old age.